THE CORRELATION BETWEEN ENGLISH LEARNING MOTIVATION AND ENGLISH PROFICIENCY ACHIEVEMENT OF ENGLISH STUDY PROGRAM STUDENTS - Deborah Purwanti; Hilda Puspita; Mulyadi . (Universitas Bengkulu, 2019)
This study is aimed at identifying English learning motivation and English proficiency achievement. Then, the researcher would like to see the correlation between the students’ motivation and their English proficiency achievement. The research was designed as quantitative correlation. Here, a total of 77 students were asked to complete the motivation questionnaire and set in a TOEFL test. The result of this research revealed that the English learning motivation of the students was in ‘high’ category. This can be seen from the grand total of mean 3.59 which indicated high intrinsic motivation as the dominant motivation. While, the scores of English proficiency achievement indicates that the students had ‘medium’ level of English Proficiency, the range score of medium level is 400-499. Another result showed that there was a significant correlation between English learning motivation and English proficiency achievement. It can be proven by rcount (0.346) > rtable (0.224), 5% level of significance; there was a correlation between students with intrinsic motivation and their English proficiency achievement, rcount (0.348) > rtable (0.233); while there was no correlation between students with extrinsic motivation and their English proficiency achievement, rcount (0.307) < rtable (0.811). It means that the correlation between English learning motivation and English proficiency achievement was in ‘weak’ level.